Interleukin-6 secreted by oral cancer- associated fibroblast accelerated VEGF expression in tumor and stroma cells - Mirkeshavarz, M.; Ganjibakhsh, M.; Aminishakib, P.; Farzaneh, P.; Mahdavi, N.; Vakhshiteh, F.; Karimi, A.; Gohari, N. S.; Kamali, F.; Kharazifard, M. J.; Shahzadeh Fazeli, S. A.; Nasimian, A. (Cellular and Molecular Biology, 2017)
Oral cancer represents the sixth most common cancer type worldwide. Patients with oral cancer express high levels of IL-6 which is associated with very poor prognosis. Previous studies illustrated that IL-6 cytokine induces angiogenesis. It has also been reported that the presence of Cancer- Associated Fibroblasts (CAFs) is essential for angiogenesis. In this study, we examined the correlation between IL-6 and CAF and the role of this correlation on VEGF production. In this study, quantitative expression level of IL-6 and VEGF in CAF and Oral Cancer Cells (OCCs) examined through Real Time PCR and ELISA and western blot analysis. In addition, maintenance and retention of IL-6 and VEGF checked out in co-culture experiment of CAF and OCC cells. These experiments demonstrated that in oral cancer, CAF cell line secretes significantly more IL-6 than OCC. Also IL-6 is a factor that causes VEGF secretion in CAF cell line. CAF is the basic and the most essential source for producing IL-6 in patients with oral cancer. Secreted IL-6 is able to induce VEGF production in both CAF and OCCs. Correlation between CAF, IL-6 and VEGF could be considered as an approach for cancer therapy.